Rapid Determination of the S-N Curve for Steel by means of the Thermographic Method - Adam Lipski (Advances in Materials Science and Engineering)
The paper presents a thermographic method of accelerated determination of the S-N curve. In the presented method, the S-N curve was developed based on energy-related parameter with the assumption of its dependency on the stress amplitude. The tests made on C45 steel and X5CrNi18-10 steel under reversed bending revealed that the S-N curve obtained by accelerated thermographic method fits inside the 95% confidence interval for the S-N curve obtained from the full test.